Dampak Kebijakan Fiskal pada Kelas Bawah dalam Novel Pabrik Karya Putu Wijaya: Marxisme - Nensilianti; Ridwan; Aprilya, Dela (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study analyzes the criticism of the impact of fiscal policy on the lower class as well as the representation of factory workers, power structures, exploitation policies, and labor alienation in the novel "Pabrik" by Putu Wijaya using a Marxist approach. Through descriptive qualitative method, data were collected from excerpts in the novel, journals, and Marxist theory books, and then analyzed using reading and note-taking techniques. The findings show that the novel depicts harsh working conditions, where factory workers have to work under pressure with minimal wages, reflecting the reality of economic and social injustice. The power structure is depicted as very authoritarian, with factory owners and management having full power and unfair policies. The exploitation of laborers becomes a central theme, where they are forced to work long hours for disproportionate wages, reflecting the practice of exploitation in the capitalist system. The alienation of laborers is also clearly depicted, with laborers feeling separated from the fruits of their labor, losing purpose in their work. The results of the analysis show that the novel "Pabrik" reflects the socio-cultural reality of society and how Marxist theory provides a deep understanding of complex socio-economic dynamics in literary works, as well as revealing the complexity of power relations and exploitation in the context of factory workers’ lives.